2013
DOI: 10.1109/tifs.2013.2242890
|View full text |Cite
|
Sign up to set email alerts
|

SVM Training Phase Reduction Using Dataset Feature Filtering for Malware Detection

Abstract: Obfuscation is a strategy employed by malware writers to camouflage the telltale signs of malware and thereby undermine anti-malware software and make malware analysis difficult for anti-malware researchers. This paper investigates the use of supervised learning machines to identify malware and investigates the problems of feature identification and feature reduction. We present several methods of filtering features in the temporal domain prior to applying the reduced feature set to the learning machines. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(30 citation statements)
references
References 19 publications
1
29
0
Order By: Relevance
“…O'Kane et al [7] found that 99.5% of variance in their data was attributed to the top 8 opcodes, providing feature reduction from the original 150 opcodes.…”
Section: A Dynamic Opcode Analysis Of Malwarementioning
confidence: 99%
“…O'Kane et al [7] found that 99.5% of variance in their data was attributed to the top 8 opcodes, providing feature reduction from the original 150 opcodes.…”
Section: A Dynamic Opcode Analysis Of Malwarementioning
confidence: 99%
“…The authors show that their results are more satisfying than the ones got by commercial antivirus software. Concerning the search and analysis of opcodes (from operation code, a portion of a machine language instruction that specifies the operation to be performed), we can mention the literature . In the work of O'Kane, it is aimed at individuating a subset of opcodes suitable for malware detection through SVM.…”
Section: State Of the Artmentioning
confidence: 99%
“…Under a filter approach, an objective function evaluates features by their information content and estimates their expected contribution to the classification task. In [26], the authors applied a prefiltering technique using eigen vectors that can reduce the feature set and therefore reduce the training effort. Since our data is binary, a feature selection algorithm that is more suitable for nominal data is preferred.…”
Section: Data and Feature Selectionmentioning
confidence: 99%